PENGGUNAAN MONITOR DETAK JANTUNG DALAM INTENSITAS 500 METER PADA ATLET CANOEING STKIP PASUNDAN CIMAHI - Yasin, Syahid Nur (STKIP Pasundan, 2019)
The use of Heart Rate monitor technology has developed rapidly in the world of sports. However, there are still few accomplished sports coaches who use it during their coaching, although it can help the trainer to know the progress of the athlete's movements. This research is a pilot study that aims to determine the motion intensity of canoeing athletes by using a Heart Rate monitor in the PE training process. A total of 24 canoeing athletes aged 15 years and above were involved in this study. The instruments used were Polar GPS (Heart Rate monitor) RC3 and Polar GPS RC3 to measure the pulse and distance of canoeing athletes during training. During the process of coaching the training canoeing athletes obtain an average pulse rate of 138.94 ± 5.48 bpm, with a maximum pulse rate of 191.75 ± 10.36 bpm. The total distance traveled by a canoeing athlete is 0.23 ± 0.10 km. Coaching training carried out on average is in the low to moderate and medium to high categories. The use of a Heart Rate monitor in the training process is strongly recommended to be able to measure the intensity of motion.